Impact of sustainable supply chain on Bangladesh readymade garments industry: a case on three factories in Narayanganj and Gazipur - Munna, Samsuddin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.